MARKET APPROACH TO EDUCATIONAL SERVICES IN POLISH HIGHER EDUCATION - Iwona WOJCIECHOWSKA (Modern Management Review, 2020)
The political changes that took place in Poland at the turn of the eighties and nineties of the twentieth century influenced not only the transformation of the political and economic systems, but also the majority of areas of social life. In higher education, the changes were the most dynamic. The purpose of this article is to look at the circumstances of the emergence of the higher education market in Poland and to consider the consequences of the market approach to the educational activity of universities. The introduction of market mechanisms in Polish higher education and changes in the socioeconomic environment mean that universities that are not able to cope with competition and growing market requirements often face serious problems. Therefore, long-term strategic thinking and the use of tools to strengthen or at least maintain the current position of universities on the market is necessary